Influence of Jet on Aerosol Retention by Pool Scrubbing Under Multihole Injector - Yuxiang Li; Yan Wu; Xuewu Cao (Frontiers in Energy Research, 2022)
In severe nuclear power plant accidents, when the containment is in a serious challenging state, the gas mixture in the containment can be injected into the spent fuel pool through the multihole injector by the containment depressurization measure, to reduce the risk of containment overpressure failure and the release of radioactivity to the environment. The pool scrubbing efficiency of aerosol under the jet regime is studied on the small-scale aerosol pool scrubbing facility, focusing on the influence of mass flux, steam fraction, submergence, particle diameter, and pool initial temperature on the aerosol decontamination factor (DF). The results show that under the jet regime, the DF value is significantly greater than that in the bubble regime and the effect of jet flow on the mechanism of steam condensation and aerosol removal of the rising zone is weak under the conditions explored. DF increases with the increase of mass flux owing to the droplet interception and inertial collision aerosol removal mechanisms. Because the high pool temperature weakens the aerosol removal by steam condensation, DF decreases with the increase of initial pool temperature under the conditions explored. Based on the experimental data and the analysis of the removal mechanism under the jet regime, an empirical model of aerosol DF considering mass flux, steam fraction, pool temperature, submergence, and particle size is established and verified by the international experiments. The proposed model can be used to calculate DF in the process of containment overpressure discharge.